DEVELOPMENT OF INTERACTIVE QUIZZES BASED ON AUGMENTED REALITY THROUGH USE TIKTOK FILTERS FOR REDUCE STUDENTS' MATH ANXIETY - Firlinda Priyantini; Hepsi Nindiasari; Maman Fathurrohman (EMTEKA: Jurnal Pendidikan Matematika, 2026)
The research conducted is a development research that aims to develop Augmented Reality-based interactive quiz media through the use of TikTok filters to reduce students' mathematical anxiety. The development model used in this study is the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were seventh grade students of SMPN 2 Ciruas. The data collection instruments used were media feasibility questionnaire, media practicality, and media effectiveness. The feasibility test was conducted to 4 expert validators, namely 2 material expert validators and 2 media expert validators. The practicality test was conducted to 2 teachers and 30 students of grade VII of SMPN 2 Ciruas. The effectiveness test was conducted by 30 students of grade VII of SMPN 2 Ciruas. The results of the feasibility test by material experts amounted to 88.46% with very feasible criteria and the feasibility test by media experts amounted to 93.75% with very feasible criteria. The results of the media practicality test by the teacher were 96.15% with very feasible criteria and the student practicality test was 81.18% with very feasible criteria. The normality test results on (pre-survey) obtained a significance value of 0.134 and on (post-survey) obtained a value of 0.591. These results indicate that the significance value of pre and post . The results of the paired sample T-Test analysis showed that namely . It can be concluded that there is an effect of developing Augmented Reality-based interactive quiz media through the use of TikTok filters to reduce students' mathematical anxiety. Based on the results of the feasibility test, practicality, and effectiveness of the media, the media in the form of Augmented Reality-based interactive quiz through TikTok Filter Utilization can be used to reduce students' mathematical anxiety. Keywords: Interactive Quiz; Augmented Reality; Mathematical Anxiety.